Workshop Teknik Presentasi Sebagai Komunikasi Persuasif Bagi Kelompok Masyarakat Peduli Iklim Bumiku Satu - Rindana Intan Emeilia; Arina Muntazah; Novalia Novalia; Anggie Ayu Astria Latuperissa (LPPM Universitas Dharma Andalas, 2023)
Climate change is an environmental phenomenon that is recognized as a threat to human life. Various efforts have been made by the government to prevent the impacts of climate change, including by establishing the Climate Village Program (ProKlim). Community participation is one of the important indicators in supporting the successful implementation of ProKlim. Therefore, presentation skills in order to persuade the surrounding community to be involved in ProKlim activities are needed by the participants and board members. With presentations that are carefully prepared, mature, attractive and clear, it is hoped that the contents of the message will be more easily understood by the audience. In response to this, this community service activity is considered important and strategic for the sustainability of ProKlim in the future. This Community Service Partner is the Bumiku Satu Climate Care Community Group which is located at Jl. Mango Well 1. RT 001 RW 001, Gaga Village, Larangan District, Tangerang City, Banten 15154. By holding community service in the form of presentation technique workshops as persuasive communication, the participants and members of the management of the Bumiku Satu climate care community in the Gaga Larangan village gain knowledge and increase understanding, abilities and skills regarding good presentation techniques that can be applied to persuade the public to campaign for programs or activities.